Antioxidant Content and Vitamin C of Combination Tea of Rose Flower and Katuk Leaf based on Drying Temperature Variation - Viscasari, Berliana; Ambarwati (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
Rose flowers and katuk leaves have not been maximally utilized. people only use rose flowers as ornamental plants and katuk leaves as vegetables. Though many bioactive compounds contained in both plants such as antioxidants and vitamin C. This study aims to examine the effect of drying temperature on the physical and chemical properties of tea combined with rose flowers and katuk leaves. the research method used a factorial complete randomized design (CRD) with a variation of drying temperatures of 50°C, 60°C, and 70°C for 5 hours, each repeated 3 times. the research parameters included chemical analysis, namely antioxidant levels (DPPH method), and vitamin C (iodimetry titration), as well as analysis of physical properties, namely pH value (pH meter), and evaluation of color, taste, and aroma. The results showed that drying temperature had a significant effect on antioxidant levels, vitamin C, pH value, color, and taste of tea, but had no effect on aroma. Drying temperature of 50°C produced the best quality with antioxidant content of 49.60%, vitamin C of 85.05 mg/100g, pH value of 6.56, light brown color, slightly bitter taste, and distinctive aroma of katuk leaves. In conclusion, a drying temperature of 50°C is recommended to produce rose flower and katuk leaf combination tea with the best physical and chemical quality.